Principles of Law and Principles of Application of Islamic Law - Dedi Ratno; Fadhila Umari Dwinata; Triska Nury Luthfiyah; Muhammad Shilhaj Abdul Mujib; Lutfa Fauzia Sukma (Al-Mahkamah: Islamic Law Journal, 2024)
Abstract. Law is a rule that regulates human life in everyday life, the purpose of law is to regulate, discipline people and create peace. Islamic law is a series of rules revealed by Allah SWT through the Al-Qur'an, Hadith and Sunnah of the Prophet, to guide humans on the right path, obeying Islamic law can create peace. Several legal principles in Islam: The principles of monotheism, justice, amar ma'ruf nahi munkar, freedom and liberty, equality, mutual help, tolerance. The source of this principle teaches us as Muslims not to discriminate between race, ethnicity and religion in doing good deeds.